The Borders of Tropicality - Gutiérrez Castaño, Julián (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
This article argues that the discourse of tropicality in Colombia creates boundaries and binaries between racialized and normative territories, rural peripheral areas and urban centres, and spaces that have been constructed as darker “barbaric” regions closer to sea level and whiter “civilized” regions in temperate altitudes. Nevertheless, there is nuance to the geographies of tropicality, because race is difficult to contain within urban/rural spaces. Additionally, race as a social construct that is permanently in the making, presents changes in space and time, challenging any static ideas of race in intersection with geography. In supporting the argument that the discourse of tropicality produces racialized spaces, this article addresses forced displacement and the racialization that takes place along with displacement, which implies the crossing of the “border” between the “tropics” and the cities; and how Afro-Colombians, Indigenous, and Mestiza campesinas challenge the ideas of tropicality by creating new geographies as they settle after displacement.